2023
DOI: 10.1136/bmjoq-2023-002413
|View full text |Cite
|
Sign up to set email alerts
|

Hospital staff reports of coworker positive and unprofessional behaviours across eight hospitals: who reports what about whom?

Rachel Urwin,
Antoinette Pavithra,
Ryan D McMullan
et al.

Abstract: BackgroundWorkplace behaviours of healthcare staff impact patient safety, staff well-being and organisational outcomes. A whole-of-hospital culture change programme, Ethos, was implemented by St. Vincent’s Health Australia across eight hospitals. Ethos includes a secure online submission system that allows staff across all professional groups to report positive (Feedback for Recognition) and negative (Feedback for Reflection) coworker behaviours. We analysed these submissions to determine patterns and rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…We compared the characteristics of the baseline and follow-up samples, adjusted for these factors, and undertook subgroup analyses with and without medical respondents for the key outcomes to assess the impact on the results. In our analysis of Ethos submissions across eight hospitals [ 28 ], we found similar rates of use of the Ethos reporting system (14.1 submissions/100 staff) as reported by those who responded to the survey, which indicates survey respondents had similar levels of engagement with the Program. The most frequent unprofessional behaviours reported to the messaging system were consistent with the most frequent behaviours reported in the staff surveys.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We compared the characteristics of the baseline and follow-up samples, adjusted for these factors, and undertook subgroup analyses with and without medical respondents for the key outcomes to assess the impact on the results. In our analysis of Ethos submissions across eight hospitals [ 28 ], we found similar rates of use of the Ethos reporting system (14.1 submissions/100 staff) as reported by those who responded to the survey, which indicates survey respondents had similar levels of engagement with the Program. The most frequent unprofessional behaviours reported to the messaging system were consistent with the most frequent behaviours reported in the staff surveys.…”
Section: Discussionmentioning
confidence: 73%
“…Our evaluation of the online messages showed that clinical staff had the highest rates of using the online messaging system. However, all professional groups submitted Ethos messages about unprofessional behaviours at roughly equal inter- and intra-professional rates, which is not surprising given the multidisciplinary nature of healthcare [ 28 ]. The reason we found the greatest decline in unprofessional behaviours experienced by non-clinical and managerial staff may be related to the fact that these groups had not previously been incorporated into targeted programs to reduce unprofessional behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1310 feedback for reflection submissions had previously been coded for 26 unprofessional behaviours, described elsewhere [ 16 ]. This process involved four researchers independently coding 10% of the reflection submissions to assess consistency.…”
Section: Methodsmentioning
confidence: 99%